A Multimodal Imaging Study in a Case of Bilateral Thalamic Damage With Multidomain Cognitive Impairment - Longarzo, Mariachiara; Cavaliere, Carlo; Orsini, Mario; Tramontano, Liberatore; Aiello, Marco; Salvatore, Marco; Grossi, Dario (Frontiers in Neurology, 2019)
Severe thalamic injury can determine a particular type of vascular dementia affecting multiple network dysfunctions, considered the central role of thalamus as hub for afferent and efferent stimuli. A 67-years old male patient with bilateral thalamic stroke was studied with positron emission tomography, magnetic resonance imaging and cognitive assessment, performed at baseline and at two follow-up evaluations. A pattern primarily involving thalamo-frontal connections was observed both by PET and tractography analyses. Neuropsychological evaluation demonstrated a multi-domain impairment including memory, executive functions and attention. Additionally, the patients displayed behavioral symptoms, in absence of mood alterations. Multimodal imaging assessment, revealing the metabolic and microstructural alterations that attend multidomain neuropsychological impairment, demonstrated multiple levels adaptations to bilateral vascular thalamic injury.